2021
DOI: 10.1098/rstb.2020.0322
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cumulative cultural evolution in bird song

Abstract: In studies of cumulative cultural evolution in non-human animals, the focus is most often on incremental changes that increase the efficacy of an existing form of socially learned behaviour, such as the refinement of migratory pathways. In this paper, we compare the songs of different species to describe patterns of evolution in the acoustic structure of bird songs, and explore the question of what building blocks might underlie cumulative cultural evolution of bird song using a comparative approach. We sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 134 publications
0
20
0
Order By: Relevance
“…Recognizing this, but going far beyond it, articles in this issue address the significance of cases where collective knowledge exists only at the level of the collective, and not in any one individual. The partial or variant knowledge of different individuals that this implies may be distributed across a population in space, and/or over time, with subsequent combinations thence leading to innovations that can drive CCE [ 82 , 93 , 153 155 , 159 , 160 ]. Studies are progressively revealing that how these effects play out may be shaped by numerous interacting factors including the form of social structures and networks [ 93 , 159 , 160 ], relationships between individuals such as in degree of tolerance [ 153 ] or coordination [ 157 ], adaptive biases in model selection such as conformity [ 153 , 163 ], and the socio-cognitive capabilities of participant individuals, such as theory of mind [ 29 , 158 ] and inventiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing this, but going far beyond it, articles in this issue address the significance of cases where collective knowledge exists only at the level of the collective, and not in any one individual. The partial or variant knowledge of different individuals that this implies may be distributed across a population in space, and/or over time, with subsequent combinations thence leading to innovations that can drive CCE [ 82 , 93 , 153 155 , 159 , 160 ]. Studies are progressively revealing that how these effects play out may be shaped by numerous interacting factors including the form of social structures and networks [ 93 , 159 , 160 ], relationships between individuals such as in degree of tolerance [ 153 ] or coordination [ 157 ], adaptive biases in model selection such as conformity [ 153 , 163 ], and the socio-cognitive capabilities of participant individuals, such as theory of mind [ 29 , 158 ] and inventiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of CCE in the realm of bird song, Williams & Lachlan [ 155 ] suggest that both these aspects—benefits to practitioners, and benefits to the behaviour patterns in the form of transmissibility ( figure 1 )—may be in play in varying contexts. Detailed comparative analyses across different songbird studies reveal how evolutionary changes in song structures emerge through collective occurrences across populations in innovations, copying errors, cultural drift, learning biases and/or the selective advantages of some variants.…”
Section: The Scope Of the Current Journal Issuementioning
confidence: 99%
“…[ 63 ]; Whiten et al [ 64 ]; Wild et al . [ 65 ]; and Williams & Lachlan [ 66 ] in the present special issue), this manuscript particularly focuses on the role of network topology on collective cognitions in humans, leaving out the evolutionary framework. That said, it is reasonable to hypothesize that human brains have evolved to handle the cognitive demands of navigating complex social networks, and that vice versa, perhaps the demand of adapting to the growth of social networks contributed to broader practices and cultures of learning and navigating complex networks.…”
Section: Navigating Social and Non-social Topologies: Common Mechanisms?mentioning
confidence: 99%
“…Further, a comparative transmission chain study of baboons and children using a non-copying task found that basic features of CCE arose from different cognitive mechanisms in humans and non-humans [ 40 ]. Thus, it may be that a variety of mechanisms can underlie the transmission of complex cultural behaviours, including the social learning of simpler behaviours and reconstruction of more complicated sets of behaviours (for a similar process in birdsong see [ 88 ], this issue). Anyone who has received professional training in a skill can attest to the critical role of individual learning through practice after initially observing a teacher.…”
Section: Discussionmentioning
confidence: 99%